2022
DOI: 10.1108/ejm-03-2021-0153
|View full text |Cite
|
Sign up to set email alerts
|

Exploration, exploitation, ambidexterity and the performance of international SMEs

Abstract: Purpose This study aims to examine how international small and medium-sized enterprises (ISMEs) improve adaptive marketing capabilities (AMCs) through exploration, exploitation and ambidexterity (EEA) and thereby increase exporting performance. In addition, the present study attempts to examine conditions under which EEA can more effectively improve AMCs. Design/methodology/approach The theoretical model was tested by using survey data collected from 119 ISMEs based in the U.S. Partial least squares structur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(5 citation statements)
references
References 104 publications
0
5
0
Order By: Relevance
“…The ambidextrous view of strategies has been proposed in international business studies (Choi et al, 2020;Huang and Cantwell, 2017;Luo and Rui, 2009;Su et al, 2022). International business scholars suggest that firms may positively adopt ambidextrous strategies to internationalize and expand their market, being the organization able to overcome the different trade-offs in going global (i.e.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The ambidextrous view of strategies has been proposed in international business studies (Choi et al, 2020;Huang and Cantwell, 2017;Luo and Rui, 2009;Su et al, 2022). International business scholars suggest that firms may positively adopt ambidextrous strategies to internationalize and expand their market, being the organization able to overcome the different trade-offs in going global (i.e.…”
Section: Introductionmentioning
confidence: 99%
“…The ambidextrous view of strategies has been proposed in international business studies (Choi et al. , 2020; Huang and Cantwell, 2017; Luo and Rui, 2009; Su et al. , 2022).…”
Section: Introductionmentioning
confidence: 99%
“…An assessment of the effectiveness of EPPs is an important research focus in the contemporary export marketing literature (Balabanis et al, 2004; Freixanet, 2022; Gencturk & Kotabe, 2001; Gillespie & Riddle, 2004; Lages & Montgomery, 2005; Shih et al, 2022; Su et al, 2022). This study contributes to international marketing theory by explaining how EPPs can influence firm EP through the development of export knowledge, managers’ positive perceptions of exporting and export markets, and export commitment.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, market exploitation also encourages resources to respond quickly to market needs and develop products for future customers (Solís-Molina et al, 2018;Zhang et al, 2015). Several studies have shown that market exploitation effectively increases competitive advantage and marketing performance (Ambroise et al, 2020;Griffith et al, 2021;Su et al, 2022). The ability to survive and compete depends on the quality of strategic resources in exploring market opportunities (Ozkaya et al, 2015;Rakthin et al, 2016).…”
Section: Preemptive Market Exploitability: Resource Advantage Theory ...mentioning
confidence: 99%